2020
DOI: 10.3390/ani10040576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amniotic Injection of N-Carbamylglutamate on Meat Quality of Broilers

Abstract: The current study was performed to determine the influence of amniotic injection of N-carbamylglutamate (NCG) on meat quality of pectoral muscle in broilers. A total of 792 alive broiler embryos at 17 d of incubation were assigned to three treatments randomly (non-injected control, saline-injected control, or NCG-injected treatment). The two injection treatments were an injection with 0.1 mL 0.85% aseptic saline alone or containing 2 mg NCG per egg at 17.5 d of incubation. After hatching, 72 healthy male chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…Drip loss can be a good indicator of water holding capacity. In agreement with our results, reduced drip loss was observed in broilers with an amniotic injection of NCG [ 37 ]. A previous study also found that reduction of drip loss was associated with declined MDA level in porcine longissimus dorsi by supplementation of NCG [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Drip loss can be a good indicator of water holding capacity. In agreement with our results, reduced drip loss was observed in broilers with an amniotic injection of NCG [ 37 ]. A previous study also found that reduction of drip loss was associated with declined MDA level in porcine longissimus dorsi by supplementation of NCG [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our results, reduced drip loss was observed in broilers with an amniotic injection of NCG [ 37 ]. A previous study also found that reduction of drip loss was associated with declined MDA level in porcine longissimus dorsi by supplementation of NCG [ 37 ]. The reduction of cooking loss was contributed to protein solubility, primarily collagen [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Its supplementation had positive effects on growth performance and tissue development of broiler chicks (6). Its amnion injection improved the meat quality of broiler chicks (7). Additionally, feeding roosters with NCG-containing diet was beneficial to regulate the levels of circulating reproductive hormone and improve the development of sexual organ (8).…”
Section: Introductionmentioning
confidence: 99%
“…Given the low NAG activity in the intestines of piglets, post-weaning arginine requirements often remain inadequately fulfilled, rendering arginine an essential amino acid for piglets [12]. Research conducted on poultry has indicated that NCG can enhance the performance and egg quality as well as the antioxidant capacity of laying hens [13,14]. Studies using NCG in weaned piglets have found that NCG may promote intestinal growth and improve growth performance [6].…”
Section: Introductionmentioning
confidence: 99%